Complement Receptor 3 Has Negative Impact on Tumor Surveillance through Suppression of Natural Killer Cell Function - Liu, Cheng-Fei; Min, Xiao-Yun; Wang, Naiyin; Wang, Jia-Xing; Ma, Ning; Dong, Xia; Zhang, Bing; Wu, Weiju; Li, Zong-Fang; Zhou, Wuding; Li, Ke (Frontiers in Immunology, 2017)
Complement receptor 3 (CR3) is expressed abundantly on natural killer (NK) cells; however, whether it plays roles in NK cell-dependent tumour surveillance is largely unknown. Here, we show that CR3 is an important negative regulator of NK cell function, which has negative impact on tumour surveillance. Mice deficient in CR3 (CD11b-/- mice) exhibited a more activated NK phenotype and had enhanced NK-dependent tumour killing. In a B16-luc melanoma-induced lung tumour growth and metastasis model, mice deficient in CR3 had reduced tumour growth and metastases, compared with WT mice. In addition, adaptive transfer of NK cells lacking CR3 (in to NK deficient mice) mediated more efficient suppression of tumour growth and metastases, compared with the transfer of CR3 sufficient NK cells, suggesting that CR3 can impair tumour surveillance through suppression of NK cell function. In vitro analyses showed that engagement of CR3 with iC3b (classical CR3 ligand) on NK cells negatively regulated NK cell activity and effector functions (i.e. direct tumour cell killing, antibody-dependent NK-mediated tumour killing). Cell signalling analyses showed that iC3b stimulation caused activation of SHIP-1 and JNK, and suppression of ERK in NK cells, supporting that iC3b mediates negative regulation of NK cell function through its effects on SHIP-1, JNK and ERK signal transduction pathways. Thus, our findings demonstrate a previously unknown role for CR3 in dysregulation of NK-dependent tumour surveillance and suggest the iC3b/CR3 signalling is a critical negative regulator of NK cell function and may represent a new target for preserving NK cell function in cancer patients and improving NK cell-based therapy.